2020
DOI: 10.3390/su12072674
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sustainability and Customer Engagement in the Online Shopping Environment: The Rational and Emotional Perspectives

Abstract: As increasing numbers of customers pay attention to product and service sustainability when shopping online, more and more firms in the online market engage in promoting perceived sustainability to establish close customer relationships. Prior studies implied the effects of perceived sustainability on transactional customer relationships, however, the role of perceived sustainability in influencing nontransactional customer relationships has received little attention. Drawing on existing conceptual models, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 62 publications
1
38
2
1
Order By: Relevance
“…If one company has developed strategies to protect the environment or has gained ISO 14001/environmental certification, the others operating in the same industry will try to follow that company; firms try to keep pace with their competition. Results related to boards of directors' concern are consistent with the previous arguments of Ricart, Rodríguez, and Sanchez [75]; Aragon-Correa, Matias-Reche, and Senise-Barrio [59]; and Kassinis and Vafeas [26]. The BOD's concern plays a critical role in ensuring the integration of the firm's strategy and sustainable development.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…If one company has developed strategies to protect the environment or has gained ISO 14001/environmental certification, the others operating in the same industry will try to follow that company; firms try to keep pace with their competition. Results related to boards of directors' concern are consistent with the previous arguments of Ricart, Rodríguez, and Sanchez [75]; Aragon-Correa, Matias-Reche, and Senise-Barrio [59]; and Kassinis and Vafeas [26]. The BOD's concern plays a critical role in ensuring the integration of the firm's strategy and sustainable development.…”
Section: Discussionsupporting
confidence: 85%
“…One of the most important findings of the current study is the insignificant relationship of customers', activists', and media concern with top management commitment and corporate environmental strategies. This result is not consistent with the previous findings of many researchers, i.e., [7,8,28,36,[73][74][75]. Some of the recent studies from China [76], Korea [77], and Pakistan [78] have also found customer pressure as an insignificant predictor of e-commerce adopting intentions to green innovation.…”
Section: Discussioncontrasting
confidence: 85%
“…Our results informed airport retail practitioners that they should vigorously make considerable efforts to enhance the level of diverse attributes of duty-free stores such as attractive physical environments (e.g., comfortable ambient conditions, neatness, cleanliness, comfortable lighting, and layout) and excellent employee/encounter services (e.g., service efficiency, sales staff knowledge of products and their attributes, and effective interaction and communication skills) to be superior to those of other alternative shopping locations (e.g., department stores, city shopping districts, duty-free stores in a city/local destination). Moreover, travelers also place great importance on shared values and social relationships with brands when purchasing products [52], due to the fact that people will give preference to retailers that contribute to the environment or products with organic labels [16]. This also enables to illustrate that the emphasis on sustainability by people has gradually increased [53].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, tangibles (e.g., interior design, décor, ambience, atmospherics), products (functionality, diversity/availability, product reliability), and staff (friendliness, helpful attitude, knowledge, efficiency) can be the important attributes of retail stores/shopping places [6,14,15]. Consequently, within limited time and space (airport), the more prominent exposure created by the retail store, the position of the retail store within the airport, the overall airport terminal decoration/layout space, and the services offered by the airport stimulate the behavioral intentions of travelers toward airport retail stores as a way to generate positive/negative perceived evaluations [16][17][18][19].…”
Section: Literature Review 21 Perceived Performance Of Airport Retail Storesmentioning
confidence: 99%
“…Being truly committed to sustainability is imperative for destinations [42], and being perceived as sustainable by visitors is paramount [12]. Perceived sustainability is the customer's perceptions of a certain product and/or service's performance related to the environment [14,19,43]. The perception of sustainability in tourism is a key concept that differs from one consumer to another, as it is based on the stakeholders affective-cognitive assessment, regarding sustainability policies applied to a specific destination [19].…”
Section: Perceived Sustainability In Tourismmentioning
confidence: 99%